2023
DOI: 10.1093/ijnp/pyad008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Electroconvulsive Seizures on Plasticity-Associated Gene Expression and Perineuronal Nets Within the Hippocampi of Young Adult and Middle-Aged Sprague-Dawley Rats

Abstract: Background Electroconvulsive seizure therapy is often used in both treatment-resistant and geriatric depression. However, preclinical studies identifying targets of chronic electroconvulsive seizure (ECS) are predominantly focused on animal models in young adulthood. Given that putative transcriptional, neurogenic and neuroplastic mechanisms implicated in the behavioral effects of chronic ECS themselves exhibit age-dependent modulation, it remains unknown whether the molecular and cellular ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Surprisingly, however, both pretreatment CT and the early increase in CT seem to represent predictive biomarkers of the clinical response to antidepressants(Phillips et al, 2015) suggesting that various processes can underlie its clinical effectiveness. Neuroplasticity, including the processes of neurogenesis, synaptogenesis, dendrogenesis, gliogenesis, and angiogenesis, has been hypothesised to be the biological mechanism for the effects of ECT on CT (Hellsten et al, 2005; Jaggar et al, 2023; Wennström et al, 2004; Zhang et al, 2023). In particular, animal studies have reported that rats subjected to electroconvulsive stimulation show increased genesis of hippocampal neurons with the potential for long-term survival (Altar et al, 2003; Madsen et al, 2005; Olesen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, both pretreatment CT and the early increase in CT seem to represent predictive biomarkers of the clinical response to antidepressants(Phillips et al, 2015) suggesting that various processes can underlie its clinical effectiveness. Neuroplasticity, including the processes of neurogenesis, synaptogenesis, dendrogenesis, gliogenesis, and angiogenesis, has been hypothesised to be the biological mechanism for the effects of ECT on CT (Hellsten et al, 2005; Jaggar et al, 2023; Wennström et al, 2004; Zhang et al, 2023). In particular, animal studies have reported that rats subjected to electroconvulsive stimulation show increased genesis of hippocampal neurons with the potential for long-term survival (Altar et al, 2003; Madsen et al, 2005; Olesen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, both pretreatment CT and the early increase in CT seem to represent predictive biomarkers of the clinical response to antidepressants (Phillips et al, 2015), suggesting that various processes can underlie its clinical effectiveness. Neuroplasticity, including the processes of neurogenesis, synaptogenesis, dendrogenesis, gliogenesis, and angiogenesis, has been hypothesised to be the biological mechanism for the effects of ECT on CT (Wennström et al, 2004;Hellsten et al, 2005;Jaggar et al, 2023;Zhang et al, 2023). In particular, animal studies have reported that rats subjected to electroconvulsive stimulation show increased genesis of hippocampal neurons with the potential for long-term survival (Altar et al, 2003;Madsen et al, 2005;Olesen et al, 2017).…”
Section: Biological Significance Of Ct Findingsmentioning
confidence: 99%